Exceptional reservoir quality in HPHT reservoir settings: Examples from the Skagerrak Formation of the Heron Cluster, North Sea, UK. (November 2016) - Stricker, Stephan; Jones, Stuart J.; Sathar, Shanvas; Bowen, Leon; Oxtoby, Norman
Abstract: As the exploration of hydrocarbons moves into more complex and deeper basinal settings the need to understand the effect of high temperatures and high pressures on reservoir quality and rock properties becomes even more important. The fluvial channel sandstone reservoirs of the Skagerrak Formation in the Central North Sea exhibit anomalously high porosities and permeabilities considering their depth of burial (>3500 m below sea floor). Despite the complex depositional setting, diagenetic history, high overpressure and temperatures encountered in the Skagerrak Formation, hydrocarbons are currently being produced. The Skagerrak Formation reservoirs used in this study have encountered overpressures of >40 MPa and temperatures up to ∼185 °C at present day maximum burial. To identify the role played by the high pressure and high temperature encountered in the reservoir sandstones a multidisciplinary approach involving petrographic, fluid inclusion, and burial history modelling studies has been adopted. Our interpretation of the results is that the generation of shallow overpressure in these fields limited mechanical compaction and also played an important role in minimizing pressure solution in the chemical compaction regime as evidenced by reduced quartz cementation. Fluid inclusions found in the quartz overgrowths indicate late-stage development with temperatures of formation in the range 130 to 170 °C coincident with late-stage deeper burial. Hydrocarbon emplacement occurred after quartz cementation and has had little to no effect on porosity preservation. The formation of well-developed authigenic chlorite (>70% surface coating) and, to a lesser extent illite clay coats with burial had a positive effect on porosity preservation even though permeability was marginally reduced in the illite-rich sandstones. A schematic porosity and quartz cement evolution model has been developed which allows for pre-drill prediction of reservoir quality in the Heron Cluster and provide valuable insights for other complex high-pressure high-temperature reservoirs.